ANALISIS POTENSI DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN (PBB P2) DI KABUPATEN GUNUNGKIDUL - Fitriani Hatta; Dewi Amalia (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2015)
According to the law number 28 year 2009 on local taxes and levies, building and land tax is 5 types namely P2 and P3. PBB P2 is the rural and urban areas, PBB P3 is the agricultural sector, fisheries, and mining. PBB P2 central tax formerly be transferred to local taxes. The regulation is effective from the beginning of 2014. Several regions had already been made since the transitional PBB P2 2012. One of the regions that conducted the transfer is in Yogyakarta. The purpose of this research was to study, analyze and concluded about potential of tax in Kabupaten Gunungkidul PBB P2 in 2014 and about the contribution of the PBB P2 in Kabupaten Gunungkidul last year until the year 2014. Based on calculations on the results of potential PBB P2 2104 year, the determination of the target and the realization of tax revenue PBB P2 in 2014 is far from the existing potential. A comparison of potential PBB P2 and the target of PBB P2 is 24,49 %, it means the determination of the target of PBB P2 is far from the existing potential. A comparison of the potential and the PBB P2 is 21,06 percent, it means the realization of tax revenue PBB P2 is far from the existing potential. In accordance with the results of the calculation of the potential research Abdullah (2012) said that when the budget income, the head of units tend to determine the target under the potential income actually. The calculation on the contribution indicate the percentage of PBB P2 in Kabupaten Gunungkidul from 2011 up to 2013 has been steadily declining. It means the role of PBB P2 or other contributions to the local revenue starting the year 2011 up to 2013 the less. This is because the realization of local revenue in Kabupaten Gunungkidul from 2011 until 2013 also rose, so as to cause the contribution of PBB P2 to local government revenue decline, although the realization of tax revenue PBB P2 increase from year 2011 up to 2013 .